The Reaction of Benzylcyamide with Chalchone - Sukhwal, Sudha; Vyas, Rajesh; Kothari, Seema; Verma, B.L. (Asian Journal of Chemistry, 2010)
The reaction of benzylcyanide with chalcones (I) was reinvestigated. Depending upon the reaction conditions and chalcones (I a-c) either α-phenylcinnamonitrile (IlIa) or the open chain Michael adduct (IV) was obtained. The structures of all the compounds have been established by elemental analysis and spectral data.